KERJASAMA ANTARDAERAH UNTUK MENINGKATKAN PEMBANGUNAN DAERAH DAN PELAYANAN PUBLIK DI KAWASAN PERBATASAN - Maria AP. Sari, Andi Wahyudi & (Pusjar SKPP Lembaga Administrasi Negara, 2011)
This study is aimed to identify regional cooperation models which are implemented by district governments within the framework of regional development, to conduct public service in the border zone, and to evaluate the effectivity of regional cooperation in achieving its goals. This study combines two research methods, i.e. descriptive analysis method with qualitative approach, and evaluation method with formal evaluation approach. Data are collected by conducting Focus Group Discussion (FGD) and supported by secondary data. Results of this study are: (1) implementation of regional cooperation among district governments in East Java and Central Java border zone is applied into regional cooperation boards (BKAD); (2) mutual interest to develop and togetherness in solving problems are basic reasons to make a regional cooperation agreement; (3) regional cooperation effectivity of the border zone is still low, due to sinergity and sincronising problems in development planning among district governments, so they affect cooperation implementation when it comes to technical operational aspects in the sectoral level.Keywords: regional cooperation, public service, regional development, border zone.Studi ini bertujuan untuk mengidentifikasi model kerjasama yang diterapkan oleh kabupaten dalam rangka pembangunan daerah dan pelayanan publik di kawasan perbatasan serta mengevaluasi sejauh mana efektivitas kerjasama itu dibandingkan tujuan dan sasaran yang telah ditetapkan. Studi ini menggunakan perpaduan metode analisis deskriptif dengan pendekatan kualitatif dan metode evaluasi dengan pendekatan evaluasi formal. Data dikumpulkan melalui FGD dan data- data sekunder. Hasil studi ini menyimpulkan bahwa (1) praktek kerjasama antardaerah di kawasan perbatasan Jatim dan Jateng diwujudkan dengan membentuk Badan Kerjasama Antar Daerah (BKAD); (2) kepentingan untuk maju bersama dan menyelesaikan masalah secara bersama antardaerah merupakan alasan mendasar terwujudnya kerjasama antardaerah; (3) efektivitas kerjasama tersebut masih rendah, hal ini karena masih adanya kendala sinergitas dan sinkronisasi perencanaan antardaerah sehingga berpengaruh dalam pelaksanaan kerjasama antardaerah ketika sudah menyentuh level teknis operasional di masing-masing sektor. Kata kunci: kerjasama antar daerah, pelayanan publik, pembangunan daerah, kawasan perbatasan.